Analisis Perubahan Kerapatan Vegetasi DAS Air Dingin Akibat Migrasi Penduduk Pasca Gempa Padang 30 September 2009 - Putri, Verenika Syah; Prarikeslan, Widya (Darul Yasin Al Sys, 2024)
The aim of this research is to determine changes in vegetation density due to population migration in the Air Cool watershed using the Normalized Difference Vegetation Index (NDVI) method. This research is descriptive research using a quantitative approach. Determining the level of vegetation density in the Air Winter watershed is carried out using the vegetation index score classification by Marwoto & Ginting (2009) which consists of Non-Vegetation, Low Vegetation, Medium Vegetation and High Vegetation density classes. The location of this research is in the Air Cold Watershed, Lubuk Minturun Village, Koto Tangah District, Padang City. Based on the results of the research conducted, several things can be concluded as follows. The results of the analysis of vegetation density levels obtained from image data for 2016 and 2022 consist of Non Vegetation density classes covering 102.86 ha and 12.46 ha, Low Vegetation 730.71 ha and 1279.74 ha, Medium Vegetation 399.76 ha and 5301.17 ha and High Vegetation 11559.82 ha and 6199.63 ha. This change in Vegetation Density was then also followed by an increase in population by 2493 people in Lubuk Minturun Village and 3856 people from Balai Gadang Village, as well as a reduction in the number of people living in areas close to the coastline. This significant population movement of course triggers land clearing for settlements and other land clearing activities so that the Vegetation Density changes along with population growth in an area.